Implementation of Augmented Reality for Introduction To Android Based Mammalian Animals Using The Marker Based Tracking Method - Kristian, Mikhael; Fitri, Iskandar; Gunaryati, Aris (JISA(Jurnal Informatika dan Sains), 2020)
Augmented Reality is a technology on 2-dimensional and 3-dimensional virtual objects that are combined into the real environment that is around us. With the ability of Augmented Reality that is able to change the atmosphere of children’s learning that can be used as a medium of learning in the introduction of mammals for kindergarten children. This AR can provide interesting facilities such as displaying 3-dimensional objects of these mammals along with animal sounds and animations using Smartphones, so that children can interact and be more creative in recognizing these mammals, because children experience their golden age at the age of 4 to 7 years which is a time when children begin to receive stimuli, so that children will be faster to receive and catch on learning from the introduction of these mammals by using Augmented Reality Technology. The results of testing on the Vuforia plugin and making the AR application on Unity can provide a good information result, where the use of AR can bring up mammalian objects by pointing the Smartphone at the marker, so that all mammals can be recognized properly. This shows that children’s interest around 85% in terms of UI/UX appearance, and 70% of children have no problems in running the Mammal Animal AR application